Skenario Pola Penggunaan Lahan Sawit Berbasis Neraca Air Di Desa Buntu Babang Kecamatan Bajo - Alwi, Astitha; Yumna; Sukriming Sapareng (SINTA Journal (Science, Technology, and Agricultural), 2025)
This study aims to analyze the condition of water availability in oil palm areas and assess the potential for its use for more environmentally friendly alternative crops using a water balance-based approach. The research location is in Buntu Babang Village, Bajo District, with primary data consisting of rainfall and climate data from BMKG during the period of 2014–2024. Effective rainfall analysis is conducted using Cropwat 8.0 application, while water availability calculations use the Thornthwaite & Mather water balance method. The research findings indicate that the average annual rainfall is quite high, but its distribution is uneven. The water surplus occurs from November to April, while the period of water deficit occurs from August to September. The water requirement for mature oil palm plants is an average of 82.5 mm/month. The comparison between the availability of water after the needs of oil palm are met and the water needs of alternative crops shows that the potential for intercropping corn and peanuts is limited to the months with water surplus. Corn plants have a higher chance of being developed during the seedling to vegetative phases in the wet period, while peanuts are more suitable during the seedling and flowering phases in the months with adequate water availability.